Genetics and biological characteristics of duck reoviruses isolated from ducks and geese in China - Xiaohong Sun; Jing Guo; Jinyan Shen; Mengdi Guan; Lili Liu; Yujiao Xie; Hongke Xu; Mengjing Wang; Anran Ren; Wenxi Li; Feng Cong; Xuyong Li (Veterinary Research)
Abstract The emergence and circulation of duck reovirus have caused severe threats to domestic waterfowl production because of the lethal infections they cause in ducks and geese. However, the evolution of circulating duck reoviruses and their replication and pathogenicity in domestic birds have not been fully investigated. In this study, we identified and isolated six duck reoviruses from clinical samples of sick or deceased farmed ducks and geese and sequenced their full genomes. Phylogenetic analysis revealed the evolutionary landscape of duck reoviruses and the complex reassortment of these circulating viruses with avian orthoreovirus and Muscovy duck reovirus. Animal infection studies revealed differences in the replication and pathogenicity of the reoviruses identified in this study in ducks, geese and chickens. Lethal infection with highly pathogenic viruses causes severe focal necrosis and hemorrhage in the liver, spleen, bursa of Fabricius and thymus, resulting in high mortality in inoculated birds. Importantly, chickens are susceptible to circulating duck reovirus, highlighting the potential risk of duck reovirus infection in chickens. Our study revealed the evolution, pathogenicity and potential cross-species transmission risk of duck reoviruses, further emphasizing the importance of continued and systemic surveillance at the interface of domestic waterfowl and chickens.